Hubungan Karakteristik Ibu Terhadap Kejadian Ketuban Pecah Dini Di RSUD Nene Mallomo Kabupaten Sidrap - Susilawati, Susilawati; Nurbaya, St.; Nasrayanti, Nasrayanti; Sukarta, Asmah; Kenre, Ishak (Program Studi DIV Kebidanan Fakultas Ilmu Kesehatan Universitas Muhammadiyah Gorontalo, 2023)
Premature rupture of membranes can cause potentially dangerous pregnancy complications. Premature rupture of membranes can cause mothers to give birth to babies in preterm conditions. The aim of this study was to determine the relationship between the characteristics of mothers giving birth to premature rupture of membranes at Nene Mallomo Hospital, Sidrap Regency in 2022. The type of research used in this study was a quantitative study with a cross sectional approach. Study. The population in this study were all mothers giving birth at The Nene Mallomo Regional General Hospital, Sidrap Regency, from July to December 2022 has a total of 73 people Sampling technique using total sampling. data collection techniques using primary data. Data analysis used the chi-square statistical test. The results showed that there was a significant relationship between age and premature rupture of membranes with a p value of 0.01 <0.005. variable parity with premature rupture of membranes 0.00 <0.005. occupational variable with premature rupture of membranes with a p value of 0.00 <0.005. The conclusion of this study is that the variables age, parity and occupation have a relationship with premature rupture of membranes